ADVERSE EFFECTS AND SIDE EFFECTS ON VITAMIN THERAPY: A REVIEW - Korah, Mejo C; Pv, Junaid Rahman; Rajeswari R; Behanan, Ahana; Paul, Elizabeth Phoeba; Sivakumar T (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Vitamins are essential to our day to day life. Its shortage in our body can cause many disorders, decreased enzyme activities also affects the genetic factors. Vitamins should be supplied through the diet in the required amount. If it is not supplied properly, vitamin tablets will be prescribed. And also vitamin tablets are the co-medication for therapies like anticancer, anti tubercular, anti viral anti HIV treatments. Many news papers reported that vitamin therapies are causing major health problems like nephro/ urolithiasis, it can increases mortality rates in smokers by increasing the risk of lung cancer, it can cause abortion when it is taken during pregnancy. Thus here we reviewed the adverse effects of vitamin therapy from various reported cases, books, instructions provided from various health organizations and also news papers and magazines. It can help health professionals to control and monitor the vitamin therapies and make awareness about the adverse effects and possible side effects of regular vitamin uptake to society.